(untitled) (Bangladesh Heart Journal, 2019)
Background: Importance of Physiological study by Fractional Flow Reserve (FFR) in the management of patient with coronary artery disease (CAD is well established. Objective: Angiographic-guided percutaneous coronary intervention (PCI) is a common practice in Bangladeshi interventional era. Data on Pre-PCI physiological study by Fractional Flow Reserve (FFR) in our patient is not available. Therefore, our primary aim was to perform pre-PCI FFR to assess the angiographically significant coronary stenosis and thus to avoid inappropriate stenting. Methods: Total 22 patients (Male 20, Female 2) were enrolled in this observational non-randomized prospective cohort. Patient who had angiographically significant lesion, planned for physiological study by pre-PCI FFR. Cut off value for FFR were clinically significant only if Pd/Pa ratio <0.75 and differed stenting if > 0.76-0.80 or above. Results: In the studied patient population, FFR done in total 27 vessels of 22 patients. Among the vessel wise FFR distribution were in LAD 67%(18), LCX 14.8%(4), RCA 14.8%(4) and Ramus Intermedius 3.7% (1). FFR was nonsignificant (<0.75) in 59% (13) patients and significant (>0.75) were in 41%(9) patients. Conclusion: In this single center, very preliminary observational prospective cohort of non-randomized study, we found, that FFR is an important aid to perform PCI in patient with angiographically significant coronary lesion, and to avoid inappropriate stenting of insignificant stenosis by physiological study. Thus, to reduce cost and untoward effects of inappropriate stenting. Bangladesh Heart Journal 2019; 34(1) : 37-43